Ultrasound Combined With Microbubbles Increase the Delivery of Doxorubicin by Reducing the Interstitial Fluid Pressure. Issue 2 (June 2019) - Xiao, Nina; Liu, Jianhua; Liao, Lianlian; Sun, Jimei; Jin, Wenhui; Shu, Xian
Abstract : Abstract: The aims of this study were to determine the change of interstitial fluid pressure (IFP) after therapy using pulsed low-frequency ultrasound combined with microbubbles and to determine the change of doxorubicin penetration in VX2 tumor. In this study, all 48 tumor-bearing rabbits were divided randomly into 6 groups (n = 8 per group). These 6 groups include doxorubicin therapy together with ultrasound combined with microbubble treatment group (Ad-US-MB treatment group), US-MB treatment group, US treatment group, MB treatment group, doxorubicin treatment group (Ad treatment group), and blank control group. The animals were intravenously injected with doxorubicin hydrochloride, and then the tumors of the animals were disposed by low-intensity ultrasound and mirobubbles for 10 minutes. The IFP of tumor tissues in rabbits was detected before and after intervention. Rabbits in each group were sacrificed immediately after treatment. The concentration and the distribution of doxorubicin were detected. The tumor IFP was significantly lower than that before treatment in the Ad-US-MB treatment and US-MB treatment groups ( P = 0.01, P = 0.013). Ultrasound combined with microbubble increased the concentration of doxorubicin in the sample of the Ad-US-MB treatment group compared with the Ad treatment group ( P < 0.05). In immunofluorescent staining section, high concentrations of doxorubicin were observed mainly around the blood vessels, and some were even discovered at a farther area in the Ad-US-MB treatment group. The pulsed low-frequency ultrasound combined with the microbubbles enhances the vascular clearance of particles into the tumor interstitium by reducing IFP.